IDENTIFIKASI KESUBURAN TANAH UNTUK PENGEMBANGAN TANAMAN HIAS HEBRAS (Gerbera jamensonii) DI KELURAHAN LANSOT, TOMOHON SELATAN - Cherise Paat; Diane Pioh; Wiesje Kumolontang (COCOS, 2019)
Abstract This research aims to acknowledge soil fertility of land for the development of Hebras (Gerbera jamensonii) decorative plant in Lansot district, of South Tomohon also to support Tomohon government programs for City of tourism and City of flowers. Soil fertility observed to soil physics to wit texture and soil permeabilities and soil chemical properties is pH, Organic Materials, nitrogen, phosphor, and potassium (K). The study was carried out during September to November 2019 in two places that are Lansot District, of South Tomohon to take the samples and Soil Science Laboratory Faculty of Agriculture, Sam Ratulangi University Manado to analysis the samples. The method used in this study is survey method by took the samples using Land use maps and the data are discussed descriptive. The final result by this research are showing that the soil in Lansot District of South Tomohon has silt loam texture and it has moderate permeability. Soil pH has a slightly sour criteria for range 6,19 – 6,35. Low and high levels of organic materials, N content is available medium, medium P and K is available in sufficient soil. The conclusion of this research it is known that soil fertility of the land for the development of Hebras (Gerbera jamensonii) houseplant in Lansot District of South Tomohon are suitable because the nutrients are readily available in soil. The development of the decorative plant will also support the City’s Government program of Tomohon as the City of tourism and the City of flowers. Key word : Soil Physics, Chemical, Hebras Plant (Gerbera jamensonii)